2019
DOI: 10.1021/acsomega.9b02390
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Reactions of a Benzodehydrotropylium Ion–Co2(CO)6 Complex

Abstract: A series of 7-methylenedehydrobenzo[7]annulen-5-ol hexacarbonyldicobalt complexes were generated by Hosomi–Sakurai reactions of allylsilanes containing o-alkynylarylaldehyde-Co2(CO)6 complexes. One of the cyclization products was converted into its corresponding dihydrobenzo[7]annulen-7-ol hexacarbonyldicobalt complex, an immediate precursor to a benzodehydrotropylium–Co2(CO)6. The cation was generated in situ and reacted with four nucleophiles, and its aromatic stabilization was determined by computational me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…It was reported that the generation, trapping, and evaluation of a dehydrotropylium ion resulted in a reduced level of aromatic stabilization. The Jones group produced η 2platinum (0), palladium(0), and zirconium(II) complexes of a dehydrotropylium ion or similar cations that exhibit no to moderate C−C bond alternation (Figure 6) [54]. For a moderate Swern-type oxidation of a range of alcohols (8b), a novel dimethyl sulfoxide activation technique using 1,1-dichlorocycloheptatriene (8a) has been devised (Figure 7).…”
Section: Reactivity Of Tropylium Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the generation, trapping, and evaluation of a dehydrotropylium ion resulted in a reduced level of aromatic stabilization. The Jones group produced η 2platinum (0), palladium(0), and zirconium(II) complexes of a dehydrotropylium ion or similar cations that exhibit no to moderate C−C bond alternation (Figure 6) [54]. For a moderate Swern-type oxidation of a range of alcohols (8b), a novel dimethyl sulfoxide activation technique using 1,1-dichlorocycloheptatriene (8a) has been devised (Figure 7).…”
Section: Reactivity Of Tropylium Ionmentioning
confidence: 99%
“…It was reported that the generation, trapping, and evaluation of a dehydrotropylium ion resulted in a reduced level of aromatic stabilization. The Jones group produced η 2 -platinum (0), palladium(0), and zirconium(II) complexes of a dehydrotropylium ion or similar cations that exhibit no to moderate C−C bond alternation ( Figure 6 ) [ 54 ].…”
Section: Introductionmentioning
confidence: 99%